Spatial Control of Oxygen Vacancy Concentration in Monoclinic WO3 Photoanodes for Enhanced Solar Water Splitting. (5th July 2022) - Kong, Heejung; Yang, Haechang; Park, Ji‐Sang; Chae, Weon‐Sik; Kim, Hee Yeong; Park, Jucheol; Lee, Jong Hoon; Choi, Seung Yo; Park, Miok; Kim, Hyeonwoo; Song, Youbin; Park, Hyunwoong; et al.
Abstract: Oxygen vacancies (OVs) are a mixed blessing for the photoelectrochemical (PEC) water oxidation performance of monoclinic tungsten trioxide (m‐WO3 ) photoanodes. Although it is widely accepted that a moderate concentration of OVs is beneficial for the PEC performance of the m‐WO3 photoanodes, this argument assumes a uniform distribution of OVs throughout the m‐WO3 crystal. In this case, only the overall concentration of OVs needs to be considered. However, the spatial non‐uniformity of OV defects in m‐WO3 photoanodes has not been thoroughly examined. In this study, by employing a m‐WO3 nanorod array as a model photoanode, the aim is to show that a higher OV concentration near the surface of m‐WO3 compared to that in the bulk is advantageous for the PEC performances of this material. In addition, a laser‐assisted defect control (LADC) process is employed to manipulate the spatial distribution of OVs in the m‐WO3 photoanodes to achieve enhanced PEC performances. Moreover, a one‐step laser deposition process is introduced to obtain an ultrathin FeNi oxygen evolution catalyst overlayer on the defect‐controlled m‐WO3 photoanodes, further improving PEC performance, photostability, and Faradaic efficiency. Abstract : This manuscript introduces a simple and novel scheme for oxygen vacancy engineering of monoclinic tungsten trioxide (m‐WO3 ). The proposed laser‐assisted defect control process enables the spatial distribution of oxygen vacancies in m‐WO3 photoanodes, resulting in the outstanding photoelectrochemical performance.